The Use of Mind Mapping in Social Studies Learning to Improve Creative Thinking Skills - Mayrisa Undari; Yeni Erita; Novalina INDRIYANI; Nur FADILLAH (RADINKA JAYA UTAMA PUBLISHER, 2023)
Abstract The social studies learning concept is very important for students to be able to adapt to their environment. The development of creative thinking skills in social life is something that must be developed. This study aims to discuss how the use of Mind Mapping in social studies learning can improve creative thinking. This type of research is descriptive qualitative with a literature review method which consists of several stages. First planning , where we determine the topics to be discussed, determine the criteria for the articles to be used. Second Conducting, the process of searching, selecting articles and data synthesis. The third is reporting, writing the results of a systematic literature review. Based on a study of 10 national articles on the use of Mind Mapping in social studies learning to improve creative thinking skills . The results of the research conducted show that the use of Mind Mapping is effective and efficient in improving students' creative thinking skills in social studies learning